Beachgrass invasion in coastal dunes is mediated by soil microbes and lack of disturbance dependence. Issue 11 (11th November 2016) - David, Aaron S.; May, Georgiana; Schmidt, Derek; Seabloom, Eric W.
Abstract: Biological invasions are a threat to ecological communities and ecosystems, yet understanding the processes that mediate invasion and the environmental contexts in which these processes are important remains a challenge. In this study, we investigated how disturbance and biotic interactions with pathogens and microbial symbionts mediate invasion of American beachgrass ( Ammophila breviligulata ) in early‐ and late‐successional coastal dune habitats. First, we tested the effect of disturbance on biomasses of two exotic beachgrass species (the invading A. breviligulata and the established A. arenaria ) and a native beachgrass ( Elymus mollis ) by growing plants with and without a disturbance manipulation in early‐ and late‐successional habitats. We quantified root colonization by fungal symbionts and infection by plant‐parasitic nematodes to determine the effect of potential mutualists and pathogens on plant biomass. Second, we tested whether soil microbes associated with the established A. arenaria mediated A. breviligulata invasion by inoculating potted plants with microbes from early‐ and late‐successional habitat. We found no effect of disturbance on biomass of the invading A. breviligulata or native E. mollis, whereas A. arenaria biomass increased when grown with disturbance. Colonization by arbuscular mycorrhizal fungi and by fungal endophytes were poor predictors of plant biomass, and plant‐parasitic nematodes were infrequently observed. Microbe addition increased belowground biomass of A. breviligulata, but not A. arenaria, compared to control treatments. Overall, our results suggest that A. breviligulata invasion in both the early‐ and late‐successional habitat is mediated by its lack of disturbance dependence and positive effects of soil microbes. These results have important implications for other primary successional systems and contribute to our understanding of how ecological contexts influence invasion processes.